Perceived causes of career plateau in the public service - Sean Darling; Barton Cunningham (Administrative Sciences, 2023)
The purpose of this paper was to develop a better understanding of the causes of career plateau in the public service, focusing on 67 people who we determined to be career plateaued. Our interviews identified examples of incidents describing successes and interruptions in careers in developing an overall picture of the reasons for people being plateaued. We identified ten themes, which were grouped into three areas: deficiencies in experience, skills and education (four themes); competition skills (four themes); and perceptions of favoritism and discrimination (two themes). In addition to feeling plateaued because of the inability to demonstrate experience, education, and knowledge, many people offered examples of being plateaued because of the lack of interviewing skills or evidence of favoritism and discrimination. Those who are plateaued because of favoritism or discrimination verbalize feelings of disgust and frustration and illustrate a tendency to become less engaged with their work. We think that the negative impacts of favoritism or systemic discrimination have important implications because they are likely to have an impact on employees and their engagement in their work and life. However, as our results are based a sample of 67 government employees in the Canadian public service, they require verification in other settings.
Keywords: 350; career plateau; discrimination; favoritism; public service